Regulatory governance Improving the institutional basis for sectoral regulators - Córdova-Novion, César (OECD Publishing, 2003)
In recent years, many countries, both within the OECD and beyond, have reappraised their regulatory policy framework to determine whether it meets the challenges of the new regulatory environment. For utility markets previously characterised by stability and slowness to change, these challenges are arising from rapidly developing technologies, converging industries, the internationalisation of markets, and more informed and discerning consumers...